2016
DOI: 10.1182/blood.v128.22.337.337
|View full text |Cite
|
Sign up to set email alerts
|

Condensed Versus Standard Schedule of High-Dose Cytarabine Consolidation Therapy with Pegfilgrastim Growth Factor Support in Acute Myeloid Leukemia

Abstract: Background: The concept of intensive post-remission chemotherapy in acute myeloid leukemia (AML) is based on the observation that despite achievement of a first complete remission (CR) after intensive induction therapy virtually all patients relapse in the absence of further treatment. Moreover, randomized studies showed that intensive post-remission consolidation chemotherapy was superior to prolonged low-dose maintenance therapy in younger patients. With regard to consolidation therapy, the landmark study co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…Chemotherapy for Group A emphasizes cytarabine in individual doses of 1‐3 g/m 2 daily or BID for 3 days per cycle for three cycles, often given as 3 g/m 2 every 12 hours on days 1, 3, and 5. However, a German‐Austrian AML Study Group found administration of this dose on days 1, 2, and 3 to 392 patients was associated with a median 4‐day reduction in time to ANC >500 from start of chemotherapy and with fewer platelet transfusions than in 176 historical patients given the 1, 3, and 5 schedule 137 . Cytarabine doses of 1 g/m 2 twice daily for 3‐4 days for three courses after CR is achieved are very probably as effective as higher doses and/or more courses irrespective of cytogenetic group 138 .…”
Section: Therapy Issuesmentioning
confidence: 99%
“…Chemotherapy for Group A emphasizes cytarabine in individual doses of 1‐3 g/m 2 daily or BID for 3 days per cycle for three cycles, often given as 3 g/m 2 every 12 hours on days 1, 3, and 5. However, a German‐Austrian AML Study Group found administration of this dose on days 1, 2, and 3 to 392 patients was associated with a median 4‐day reduction in time to ANC >500 from start of chemotherapy and with fewer platelet transfusions than in 176 historical patients given the 1, 3, and 5 schedule 137 . Cytarabine doses of 1 g/m 2 twice daily for 3‐4 days for three courses after CR is achieved are very probably as effective as higher doses and/or more courses irrespective of cytogenetic group 138 .…”
Section: Therapy Issuesmentioning
confidence: 99%
“…We suspect that the higher values agglomerate biological phenomena that are not correctly described or fully covered by the current model. Nevertheless, the model exhibited the same behavior as in clinical trials with pegfilgrastim [5], i.e., a prolonged WBC recovery time of several days without G-CSF, compared to Figure S5.…”
Section: Discussionmentioning
confidence: 64%
“…A global sensitivity analysis was conducted to identify the impact of each parameter, respectively constant, on the variability of two model outputs [74]. The model outputs of interest were the leukemic cells in the bone marrow (x l1 ) at the end of a consolidation cycle and the nadir of circulating white blood cells similar to the two objective function terms in the optimization problem (5). The sensitivity analysis was performed in R (version 3.6.1) using the packages mrgsolve (version 0.10.0) for solving the ODE system (1) and sensitivity (version 1.17.0, sobolmartinez function) for the global sensitivity analysis.…”
Section: Sensitivity Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Our rate of hospitalization 15 Interestingly, the rate of neutropenic fever per cycle is lower than what was reported in other studies. 6,7,[10][11][12] However, there is heterogeneity in how the rate of neutropenic fever is reported. 12 The incidence of adverse events reported in our cohort is consistent with previously reported experience with HiDAC or IDAC consolidation therapy.…”
Section: Discussionmentioning
confidence: 99%